Leptusa-Arten aus Bulgarien und Griechenland (Coleoptera, Staphylinidae, Aleocharinae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 2002)
Leptusa (Stictopisalia) pirinensis sp. n. (Bulgaria: Pirin Planina), Leptusa (Stictopisalia) maleschevskaensis sp. n. (Bulgarien: Maleshevska Planina), and Leptusa (Oncopisalia) athosensis sp. n. (Greece: Mount Athos) are described and compared with related species. A second designation of a lectotype for Leptusa monachorum Bernhauer, 1912 by Pace (1989), with a different type locality, has no validity (ICZN 2000: Article 74.1.1.), a lectotype was already fixed by Pace (1983). Records from Bulgaria are reported for seven Leptusa species. L. (Roubaliusa) salonichia Bernhauer, 1914 and L. (Stictopisalia) bozdaghensis Pace, 1983 are new for Bulgaria. Records from Greece are reported for eleven Leptusa species. All the Leptusa species known from Bulgaria are listed. Nomenclatural Acts athosensis Zerche, 2002 (Leptusa (Oncopisalia)), spec. n. maleschevskaensis Zerche, 2002 (Leptusa (Stictopisalia)), spec. n. pirinensis Zerche, 2002 (Leptusa (Stictopisalia)), spec. n.